ChemInform Abstract: Synthesis of Fluorinated exo‐Glycals Through Modified Julia Olefination. Issue 35 (8th August 2013) - Habib, Samuel; Larnaud, Florent; Pfund, Emmanuel; Lequeux, Thierry; Fenet, Bernard; Goekjian, Peter G.; Gueyrard, David
Abstract Both the protecting groups as well as the presence of BF3·Et2O influence yield and E/Z selectivity of the reaction.